Cryopreserved human precision-cut lung slices provide an immune competent pulmonary test system for "on-demand" use and long-term cultures. (6th January 2023) - Patel, Vivek S; Amin, Khalid; Wahab, Adam; Marimoutou, Méry; Ukishima, Lindsey; Alvarez, Jose; Battle, Kelley; Stucki, Andreas O; Clippinger, Amy J; Behrsing, Holger P
Abstract: Human precision-cut lung slices (hPCLS), considered a highly relevant ex vivo model of the lung, offer native architecture and cells of the lung tissue including respiratory parenchyma, small airways, and immune competent cells. However, the irregular availability of donor lungs has limited the accessibility of this system. As described here, thousands of hPCLS can be created from 1 lung, cryopreserved, and used "on demand" by applying slicing and cryopreservation methodology improvements. Fresh and cryopreserved (∼7 and ∼34 weeks; F&C) hPCLS from 1 donor lung were cultured for up to 29 days and evaluated for biomass, viability, tissue integrity, and inflammatory markers in response to lipopolysaccharide (LPS; 5 µg/ml) and Triton X-100 (TX100; 0.1%) challenge (24 h) at days 1, 8, 15, 22, and 29 following culture initiation. The F&C hPCLS retained biomass, viability, and tissue integrity throughout the 29 days and demonstrated immune responsiveness with up to ∼30-fold LPS-induced cytokine increases. Histologically, more than 70% of normal cytomorphological features were preserved in all groups through day 29. Similar retention of tissue viability and immune responsiveness post cryopreservation (4–6 weeks) and culture (up to 14 days) was observed in hPCLS from additional 3 donor lungs. Banking cryopreserved hPCLS from various donors (and disease states) provides a critical element in researching human-derived pulmonary tissue. The retention of viability and functional responsiveness (≥4 weeks) allows evaluation of long-term, complex endpoints reflecting key events in Adverse Outcome Pathways and positions hPCLS as a valuable human-relevant model for use in regulatory applications.